The Impact of Green Marketing Implementation on Brand Image and Green Consumer Behavior on The Body Shop Products in Jakarta 2022 - Devi, Aninda Rosa Puspita; Margaretha, Monica; Hidayat, Noor Syamsu (Institut Transportasi dan Logistik Trisakti, 2022)
The Body Shop is a company that focuses on cosmetic products. The Body Shop is famous for the products that use natural and environmentally friendly ingredients. The Body Shop emphasizes its support in every campaign that is carried out on various environmental issues circulating around the world, and involves its consumers to participate in protecting the environment. This campaign strategy is called “Green Marketing” and is one of the pioneers in Indonesia. In this study, aims to analyze the impact of the implementation of green marketing on brand image and green consumer behavior on The Body Shop products in Jakarta. This research technique uses descriptive quantitative methods with a population of users of The Body Shop in DKI Jakarta and the sample used is 150 respondents with accidental sampling. This research uses SEM-PLS analysis tool. The results of this study prove that green marketing has a significant effect on brand image and green marketing has a significant effect on green consumer behavior.